A Gut microbiota and rheumatic diseases: new insights into pathogenesis - Pażyra, Aldona; Nowakowska, Katarzyna; Więsyk, Piotr; Oklecińska, Łucja (Quality in Sport, 2024)
Background: Rheumatic diseases are a group of disorders characterised by a loss of immune tolerance, which leads to chronic inflammation, degeneration or metabolic abnormalities in various organs or tissues. Despite the lack of clarity surrounding the causes of these diseases, both environmental and genetic factors play an important role. Recent research indicates that alterations in the composition of the gut microbiota, known as gut dysbiosis, may contribute to the development of a number of rheumatic diseases, including rheumatoid arthritis, systemic lupus, ankylosing spondylitis, systemic scleroderma and Sjögren's syndrome. The gut microbiota influences the balance between pro- and anti-inflammatory immune responses, which may have important implications for the pathogenesis of these diseases. Furthermore, studies have indicated that the composition of the gut microbiota may be associated with the response to therapies used to treat rheumatic diseases, thus opening up new avenues for the development of microbiota-targeted treatments for these conditions. Aim of the study: The objective of this review is to investigate the impact of the gut microbiota on the pathogenesis of rheumatic diseases and to evaluate potential therapies targeting the manipulation of the gut microbiota. Material and methods: The present study is based on literature available in scientific databases from 2019-2024, such as PubMed, Corchane Library and Google Scholar.Results and conclusions: A growing body of evidence suggests a potential link between the gut microbiota and rheumatic diseases. Patients often exhibit a reduced ratio of Firmicutes to Bacteroidetes and abnormal numbers of Bacteroides. Molecular mimicry and a potential association with short-chain fatty acids have also been observed. Further human studies are needed to more fully understand the role of the gut microbiota and potential therapeutic interventions.